'A great traffic was going on, as usual, in Whitehall': Public Places and Secret Spaces in Sherlock Holmes's London. (November 2021) - Glazzard, Andrew
Abstract : Arthur Conan Doyle is rarely considered a master of spy fiction, but several Sherlock Holmes stories were highly influential in the development of this genre in the late Victorian and Edwardian periods. This paper examines three of these stories – 'The Naval Treaty', 'The Second Stain', and 'The Bruce-Partington Plans' – and shows how they use the topography of London to explore themes of secrecy, concealment, and political power. Holmes investigates place and space in two ways: he discovers what happens behind the closed doors of government buildings like the Foreign Office in Whitehall and the Woolwich Arsenal, and he reads public spaces (like the London Underground and the streets of Westminster) to detect relationships not apparent to those lacking his criminological skills. These stories inspired contemporary and later authors of espionage fiction as they exemplify some of the purposes and pleasures of the genre – the romanticisation of bureaucracy and insights into secret history.